2011
DOI: 10.3386/w17308
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Trade on Organization and Productivity

Abstract: A firm's productivity depends on how production is organized given the level of demand for its product. To capture this mechanism, we develop a theory of an economy where firms with heterogeneous demands use labor and knowledge to produce. Entrepreneurs decide the number of layers of management and the knowledge and span of control of each agent. As a result, in the theory, heterogeneity in demand leads to heterogeneity in productivity and other firms' outcomes. We use the theory to analyze the impact of inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
142
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(163 citation statements)
references
References 49 publications
20
142
1
Order By: Relevance
“…Related to this literature, Caliendo and Rossi-Hansberg (2012) empirically …nd that exporting …rms increase the number of layers of management as a result of trade liberalization, with a more complex organizational design implying a higher …rm productivity. A relationship between organization and productivity is also present in Bloom, Sadun and Van Reenen (2012), who …nd that …rms headquartered in high-trust countries are also the ones that are more likely to decentralize decisions, eventually showing higher aggregate productivity thanks to a better reallocation of resources.…”
Section: In Terms Of Trade ‡Ows a Reading Of The Us Bea (2012) Data mentioning
confidence: 98%
“…Related to this literature, Caliendo and Rossi-Hansberg (2012) empirically …nd that exporting …rms increase the number of layers of management as a result of trade liberalization, with a more complex organizational design implying a higher …rm productivity. A relationship between organization and productivity is also present in Bloom, Sadun and Van Reenen (2012), who …nd that …rms headquartered in high-trust countries are also the ones that are more likely to decentralize decisions, eventually showing higher aggregate productivity thanks to a better reallocation of resources.…”
Section: In Terms Of Trade ‡Ows a Reading Of The Us Bea (2012) Data mentioning
confidence: 98%
“…Caliendo and Rossi-Hansberg (2012) found that liberalizing trade provides the exporter with more productivity than revenue. As such, China's increase in steel exporting might be attributed more to the goal of dominating world markets than the desire to make short-term financial gain.…”
Section: Literature Review and Backgroundmentioning
confidence: 99%
“…Caliendo and Rossi-Hansberg (2012) found that liberalizing trade provides the exporter with more productivity than revenue; anti-dumping grievances would have more credence if many of these steel organizations are losing money in efforts to simply gain markets.…”
Section: Reactions/future Studiesmentioning
confidence: 99%
“…Marin and Verdier (2008, 2012, 2014 show that globalization affects the delegation of formal and real authority in organizations. They embed the allocation of formal decision authorityà la Aghion and Tirole (1997) into models of international trade and explain how economic integration leads to the delegation of power inside firms.…”
Section: Introductionmentioning
confidence: 99%
“…Marin et al (2015) investigate how the allocation of power inside firms is affected by offshoring managers or production tasks in a small open economy model. Caliendo and Rossi-Hansberg (2012) show that exporting firms increase the control span of managers and the number of management layers within their hierarchies after trade liberalizations. Acemoglu et al (2007) analyze how technology diffusion affects firm decentralization.…”
Section: Introductionmentioning
confidence: 99%